2022
DOI: 10.3389/fpsyg.2022.1005726
|View full text |Cite
|
Sign up to set email alerts
|

Spatial cognition and the avian hippocampus: Research in domestic chicks

Abstract: In this review, we discuss the functional equivalence of the avian and mammalian hippocampus, based mostly on our own research in domestic chicks, which provide an important developmental model (most research on spatial cognition in other birds relies on adult animals). In birds, like in mammals, the hippocampus plays a central role in processing spatial information. However, the structure of this homolog area shows remarkable differences between birds and mammals. To understand the evolutionary origin of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 164 publications
1
4
0
Order By: Relevance
“…The detour task has also been suggested to reflect inhibitory control, as chicks have to inhibit their tendency to directly approach their goal in order to reach it 26 , 49 . That a spatially more complex rearing environment results in improved spatial skills is supported by previous research 13 , 15 , 16 , 32 , with possible links to neural activity in the hippocampus 17 , 18 . However, the shorter latency to solve the detour task could also be linked to a generally improved ability to solve problems as a consequence of living in a more enriched environment (reviewed by Zentall 50 ).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The detour task has also been suggested to reflect inhibitory control, as chicks have to inhibit their tendency to directly approach their goal in order to reach it 26 , 49 . That a spatially more complex rearing environment results in improved spatial skills is supported by previous research 13 , 15 , 16 , 32 , with possible links to neural activity in the hippocampus 17 , 18 . However, the shorter latency to solve the detour task could also be linked to a generally improved ability to solve problems as a consequence of living in a more enriched environment (reviewed by Zentall 50 ).…”
Section: Discussionsupporting
confidence: 57%
“…For example, aviary-reared hens are faster locating a reward in a spatial task and have greater working memory compared to individuals reared in a simple cage environment 16 . These results may be reflecting increased neural activation in the hippocampus, a brain region highly associated with spatial skills and navigation, which is seen already in day-old chicks exposed to spatially complex environments 17,18 . Thus it can be suggested that early exposure to mild stress and spatial complexity may contribute to an improved ability to cope with future stressful situations and greater ability to make the most of opportunities when they arise.…”
mentioning
confidence: 98%
“…This finding raises the possibility that a neural circuit corresponding to the trisynaptic circuit exists in the HF of birds. The current state of the avian HF, especially in chickens, was recently reviewed (see Morandi-Raikova and Mayer, 2022 ).…”
Section: The Avian Brainmentioning
confidence: 99%
“…The bird Hp and mammalian Hp have the same origin [19]. After close to 310 million years of independent evolution, although there are some differences in their structure, and the correspondence between their subdivisions is still under debate, researchers agree that the bird Hp shows homology with that of mammals [20][21][22]. Like the mammalian system, the bird Hp has access to highly processed visual information through the parahippocampal area (APH) [8,19], which provides the neural circuit basis for the formation of visual-spatial associative memory.…”
Section: Introductionmentioning
confidence: 99%